Are Rituals Causally Opaque? The Case of Ritual Fasting and Drug Use - Placek, Caitlyn Diane (Journal for the Cognitive Science of Religion, 2024)
Xygalatas (2022) states that rituals are causally opaque, meaning they have symbolic value and lack a practical outcome in the external world. In this commentary, I address my concerns with Xygalatas’ definition of ritual, which are framed as follows: first, are rituals causally opaque, or does the way researchers think and ask about rituals create a response bias? Second, if rituals consist of transparent outcomes, does this negate their classification as a ritual? Third, must a ritual lead to impractical outcomes to still be considered a ritual? I focus primarily on fasting and drug use in reference to the stated questions to illustrate the complexity underlying the definition of ritual. Using ethnographic examples, I highlight the need for further discussion of the definition of ritual to discern if causal opacity is truly necessary to establish a series of behaviors as ritualistic.